Mating changes the female dietary preference in the two-spotted cricket, Gryllus bimaculatus - Tsukamoto, Yusuke; Kataoka, Hiroshi; Nagasawa, Hiromichi; Nagata, Shinji (Frontiers in Physiology, 2014)
Most insect species exhibit characteristic behavioral changes after mating. Typical post-mating behaviors in female insects include noticeable increases in food intake, elevated oviposition rates, lowered receptivity to courting males, and enhanced immune response. Although it has been reported that mated females of several insect species including the fruit fly, Drosophila melanogaster increase the amount of food intake and change their dietary preferences, the limited number of comparative studies prevent the formulation of generalities regarding post-mating behaviors in other insects in particular amongst orthopteran species. Here, we investigated whether females of the two-spotted cricket, Gryllus bimaculatus, alter their feeding behavior after mating. Although significant differences in the amount of food intake after mating were not observed, all experimental data indicated a clear trend among crickets towards the ingestion of larger quantities of food. Geometric framework analyses revealed that the mated female crickets preferred food with higher protein content compared to virgin female crickets. This implies that this species required different nutritional demands after mating. These findings further expand our understanding of the behavioral and biological changes that are triggered in female insects post-mating, and highlight the potential for this species in investigating the molecular-based nutritional dependent activities that are linked to post-mating behaviors.